1987
DOI: 10.1111/j.1365-3180.1987.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination response of Galium spurium L. to light

Abstract: Summary The effects of intensity, duration and spectral quality of light were investigated on the germination of Galium spurium L. Light inhibited germination and the degree of this inhibition was related to the intensity and duration of exposure to light beyond the initial 36‐h imbibition period. Subsequent dry storage for up to 7 weeks and reincubation in the dark did not remove this inhibitory effect, indicating that a secondary dormancy was induced by continuous exposure to light. Germination was completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
5
20
0
Order By: Relevance
“…2, right). This is similar to other negative photoblastic seeds (Mancinelli & Tolkowsky, 1968; Malik & Vanden Born, 1987; Botha & Small, 1988).…”
Section: Discussionsupporting
confidence: 88%
“…2, right). This is similar to other negative photoblastic seeds (Mancinelli & Tolkowsky, 1968; Malik & Vanden Born, 1987; Botha & Small, 1988).…”
Section: Discussionsupporting
confidence: 88%
“…Hirinda (1959) reported 50-16% gerrnination of G. aparine in the dark, 0-4% in the light, and 39-50% under "intermediate" conditions. We found that germination of G. spurium was inhibited by light and that the degree of this inhibition was related to the intensity and duration of exposure to light (Malik and Vanden Born 1987c …”
mentioning
confidence: 87%
“…Cues for seed germination include light and soil moisture, the environmental drivers recognized as controls on M. vimineum distributions (Boyd and Van Acker 2004;Xiong and Nilsson 1999). Ground-layer litter may filter or block sunlight and/or prevent the seeds from contacting mineral soil which reduces the ability to imbibe moisture (Malik and Vandenborn 1987;Schramm and Ehrenfeld 2010;Wuest et al 1999;Xiong and Nilsson 1999). Bare soil exposure caused by perturbations such as flood scouring (Barden 1987), drought (Yurkonis and Meiners 2006) and fire The putative niche requirements and landscape dynamics of M. vimineum 477 (Glasgow and Matlack 2007) breaks down these environmental barriers and M. vimineum recruitment responds vigorously.…”
Section: Litter-layermentioning
confidence: 99%